Immunosenescence and the Susceptibility of the Elderly to Coronavirus Disease 2019 (COVID-19) - Widya Wasityastuti; Andika Dhamarjati; Siswanto Siswanto (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
A new disease caused by a newly-found coronavirus, known as Coronavirus Disease 2019 (COVID-19), has been declared as a pandemic by World Health Organization (WHO). This new disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The outbreak started in late December of 2019 and it did not take a long time until it spread to more than 200 countries in the world with over 4 million confirmed cases to date. The number keeps skyrocketing as day passes, followed by the increasing number of fatalities. Among all of the infected patients, elderly is one of the vulnerable populations. Studies reported that the risk of infection is doubled in older people. This infection-susceptible characteristic may be due to the weak immune system, therefore they lack the capabilities to fight the infection. The deterioration of immune system in elderly is known as immunosenescence. The aim of this literature review is to understand the effect of immunosenescence in the immunopathogenesis and susceptibility of elderly who are exposed to COVID-19 infection. (J Respir Indo. 2020; 40(3): 182-91)